2013
DOI: 10.3390/ijms141020543
|View full text |Cite|
|
Sign up to set email alerts
|

Combined Taurine, Epigallocatechin Gallate and Genistein Therapy Reduces HSC-T6 Cell Proliferation and Modulates the Expression of Fibrogenic Factors

Abstract: Hepatic fibrogenesis involves the activation of hepatic stellate cells (HSCs), which synthesize excess extracellular matrix and contribute to the development of liver fibrosis. In a prior study we tested the effect of combined treatment with taurine, epigallocatechin gallate and genistein on the development of alcohol-induced liver fibrosis in vitro. In this study, the biological activity of the combination of these molecules was assessed by measuring its effect on cell proliferation, fibrosis-related gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…During hepatic fibrogenesis, collagen deposition (primarily collagen types I and III) accounts for 50% of the total proteins in the fibrotic liver (Li et al, ). Therefore, we found the level of col‐1 was effectively reduced by amirolide in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…During hepatic fibrogenesis, collagen deposition (primarily collagen types I and III) accounts for 50% of the total proteins in the fibrotic liver (Li et al, ). Therefore, we found the level of col‐1 was effectively reduced by amirolide in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the MTT result showed that the activity of HSCs was increased under acidic conditions. A previous study indicated that collagen deposition mainly accounts for proteins in fibrotic liver [29]; thus, we can say that the inhibition of ASIC1a may relieve acid‐induced activated HSC activity. Our results also showed that the ASIC1a expression plasmid group aggravated the acid‐induced cell activation.…”
Section: Discussionmentioning
confidence: 82%
“…A variety of biological factors are involved in the pathogenesis of liver fibrosis. As an approach to investigate the multiple signaling pathways that may contribute to liver fibrosis, our group previously reported that combination therapy with taurine, EGCG and genistein exhibits a protective effect against liver fibrosis in vivo and in vitro ( 15 , 18 ). In the present study, the mechanistic underpinnings of this effect in HSC-T6 cells were evaluated using a proteomic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, experimental analysis of HSC activation is an important aspect of research into the pathogenesis hepatic fibrosis. Our group previously reported that combination therapy with taurine, epigallocatechin gallate (EGCG) and genistein exhibits a protective effect against alcohol-induced liver fibrosis and also reduces cell proliferation and the expression of fibrogenic factors in the rat HSC-T6 cell line ( 15 , 18 ).…”
Section: Introductionmentioning
confidence: 99%